2020
DOI: 10.1093/tropej/fmaa122
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Behavioral Impact of Lockdown and Quarantine Measures for COVID-19 Pandemic on Children, Adolescents and Caregivers: A Systematic Review and Meta-Analysis

Abstract: Background During the current ongoing COVID-19 pandemic, psychological problems like anxiety, depression, irritability, mood swings, inattention and sleep disturbance are fairly common among quarantined children in several studies. A systematic review of these publications to provide an accurate burden of these psychiatric/behavioral problems is needed for planning mitigating measures by the health authorities. Methods Different electronic databases (MEDLINE, EMBASE, We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
462
5
44

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(586 citation statements)
references
References 29 publications
17
462
5
44
Order By: Relevance
“…Starting from previous reports of negative effects of the COVID-19 lockdown on the general child and adolescent population and of the additional challenges for children with NDD, we expected worsening of emotional and behavioral profiles in all children and a more marked worsening in children at risk for NDD. Based on the previous literature, we expect worsening in specific CBCL scales, reflecting anxiety and depression [9][10][11][12]16,27], sleeping disorders [1,10], difficulty in concentrating [1,13,14,16], irritability and externalizing behaviors [1,13,14,16,33], and somatic complaints [27]. In addition, we hypothesized that some clinical, socio-demographic and environmental factors might act as protective or risk factors.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Starting from previous reports of negative effects of the COVID-19 lockdown on the general child and adolescent population and of the additional challenges for children with NDD, we expected worsening of emotional and behavioral profiles in all children and a more marked worsening in children at risk for NDD. Based on the previous literature, we expect worsening in specific CBCL scales, reflecting anxiety and depression [9][10][11][12]16,27], sleeping disorders [1,10], difficulty in concentrating [1,13,14,16], irritability and externalizing behaviors [1,13,14,16,33], and somatic complaints [27]. In addition, we hypothesized that some clinical, socio-demographic and environmental factors might act as protective or risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…The first investigations conducted during the COVID-19 outbreak revealed a wide variety of mental health issues in children and adolescents, including anxiety and depression [9][10][11][12], sleeping disorders [1,10], irritability and difficulty in concentrating [1,13,14], clinginess and excessive dependence on parents [1,13] and worries and fear that family members could contract the infection [1,13,15]. A recent meta-analysis by Panda et al [16] revealed that 34.5%, 41.7%, 42.3% and 30.8% of the children were suffering, respectively, from anxiety, depression, irritability and inattention. One study specifically compared children from the general population-both younger and older than 6 years of age-and suggested that clinging, inattention and irritability were the most severe psychological conditions displayed by children in all age groups, whereas children in the younger age group (3-6 years) were more likely than older children to manifest symptoms such as clinginess and fear that family members may contract the infection [1].…”
Section: Introductionmentioning
confidence: 99%
“…Widespread disruption to mental health services, including repurposing of staff and facilities, has been identi ed at a time when they may be needed more than ever (23). The conditions of imposed "lockdowns" may be having a negative effect on children's mental health (11), and as identi ed in this study and elsewhere (24), this is manifesting in rising psychosocial presentations at the ED, which may not be the most appropriate pathway to mental health care. As the pandemic continues to progress, policy makers and service providers must ensure the continued provision of essential health and social services, including targeted responses for those with existing conditions.…”
Section: Psychological Challenges For Staffmentioning
confidence: 59%
“…Another clinician relayed an interaction with a parent who misinterpreted the government message to stay home as including not being allowed to travel to the hospital: "she fully believed that if she was stopped by the guards [police] on the road that they would tell her to turn back" [11]. Furthermore, it was evident that parents believed hospitals were overwhelmed with COVID-19 patients.…”
Section: Fear Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation